Intergenerational Cultural Transmission: Strategi Pelestarian Budaya Aceh dalam Komunitas Diaspora Kampung Acheh di Kota Yan, Kedah Darul Aman, Malaysia - Mursyidin Mursyidin; Teuku Zulkarnaen; Naidi Faisal; Nur Hafni; Ade Ikhsan Kamil; Mustafa Kamal; Mulyadi Mulyadi; Muntasir Muntasir (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2026)
This community service activity was carried out to preserve Acehnese culture for the younger generation of the diaspora in Kampung Acheh, Kota Yan, Kedah Darul Aman, Malaysia, through Intergenerational Cultural Transmission. This activity was carried out against the backdrop of concerns about the loss of Acehnese cultural identity among the younger generation, who tend to be influenced by globalization and the process of cultural assimilation. In collaboration with the Institute of Social Sciences at Universiti Putra Malaysia, training and guidance were provided to the local community, involving young people and the older generation, related to cultural preservation in the form of preserving the Acehnese language and documenting culture in the digital field. Cultural preservation groups were formed at the village level and sustainable cultural education modules were developed. This activity is expected to be a solution to the weakening of Acehnese cultural identity among the diaspora and to strengthen its preservation in the future. This activity integrates information technology and optimization processes to accelerate cultural preservation efficiently and effectively.